The Composition and Diversity of Fresh Water Fish in The Upstream of the Bedadung River, Jember District - Setiawan, Rendy Setiawan (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2023)
The river is an irrational body of water from upstream to downstream. The upstream part of the river generally has a narrow width of the river flow, heavy air currents, the right and left banks of the river have vegetation trees, sandy rocky substrate types, and are located in the highlands or mountains. This character is also found in the Upper Bedadung River in the Argopuro Mountains. Characteristics in the upper reaches of the river are thought to affect the existence of creatures that live in it, such as fish. The purpose of this study was to determine the composition, dominance, and types of freshwater fish in the upper reaches of the Bedadung River, Jember Regency. The research method used is roaming method. The exploration was carried out at four research stations. The results showed that in the Upper S. Bedadung five species of fish were found including Channa gachua, Poecilia reticulata, Barbodes binotatus, Glyptothorax platypogon, and Nemacheilus fasciatus. The diversity of freshwater fish species in the upper reaches of the Bedadung River is moderate.